Civil humanism as a source of citizenly ideology of the cossacks - Матюхіна, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article deals with the place of civil humanism in the Renaissance culture of Ukraine, its influence on the formation of citinzenly ideology of the Cossacks.